2001
DOI: 10.21273/hortsci.36.6.1117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seedling Size Following Germination Using Computer-aided Analysis of Digital Images from a Flat-bed Scanner

Abstract: Early seedling growth rate can be used to estimate seed vigor for small-seeded vegetable and flower seeds. However, hand measurement of small seedlings is tedious and difficult to reproduce among analysts. Computer-aided analysis digital images of seedlings should improve accuracy and reproducibility. A flat-bed scanner fitted with base and top lighting provided high resolution images of even small-seeded species like petunia [Petunia ×hybrida `Blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 4 publications
(4 reference statements)
0
14
0
Order By: Relevance
“…1). Nine cuttings were sampled every 3 d for 24 d. Post-emergent root length was measured using MacRhizo (Régent Instruments, Quebec, Canada) software of digital images taken using a fl at bed scanner (Geneve and Kester, 2001). CUTTING WATER RELATIONS.…”
Section: Stages Of Root Formationmentioning
confidence: 99%
“…1). Nine cuttings were sampled every 3 d for 24 d. Post-emergent root length was measured using MacRhizo (Régent Instruments, Quebec, Canada) software of digital images taken using a fl at bed scanner (Geneve and Kester, 2001). CUTTING WATER RELATIONS.…”
Section: Stages Of Root Formationmentioning
confidence: 99%
“…Petri dishes were sealed with Parafilm and placed in a single germination chamber held at a constant 23°C at 40 µmol·s -1 ·m -2 from cool-white fluorescent lamps. Seedling growth was evaluated using computer-aided analysis of digital images (Geneve and Kester, 2001). Petri dishes were scanned and digital images acquired using a flat-bed scanner (Hewlett Packard Scanjet 4c/5, Palo Alto, Calif.) that included both base and top lighting.…”
Section: F O R M a T T E D P R O O Fmentioning
confidence: 99%
“…Gray and Steckel (1983) showed that seedling length measured by the slope test predicted field emergence in carrot as well as a controlled deterioration test. Because seed size is small for most flower crops, early seedling growth can be difficult and time consuming to measure and results can easily vary between analysts (Geneve and Kester, 2001). Use of computer-aided image analysis of seedling size overcomes many of these limitations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital imaging could provide an efficient means of capturing images and facilitating image storage for subsequent analyses. Similar technologies are being used to score germination or seedling length and to rapidly capture and store the data (Geneve and Kester 2001;McDonald et al 2001;Dell'Aquila 2004, 2007Hosomi et al 2011). …”
Section: Introductionmentioning
confidence: 99%